MENGURAI PROBLEMATIKA MASA DEPAN KEPEMIMPINAN PENDIDIKAN ADAPTIF DI ERA DIGITAL - Siswadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to examine the future challenges of adaptive educational leadership in the digital era, as well as to identify relevant challenges, opportunities, and strategies in responding to educational transformation. The research employs a qualitative approach using literature study as the primary data source. The findings reveal that adaptive educational leadership faces several major challenges, including gaps in digital literacy, limited technological infrastructure, resistance to change, regulatory complexity, and limited ability to critically evaluate digital content. However, the digital era also offers strategic opportunities, such as the use of technology for data-driven decision-making, the development of flexible and personalized learning, and expanded cross-institutional collaboration. Furthermore, leadership adaptation requires strengthening digital competencies, fostering a culture of innovation, and transforming organizational culture to become more collaborative, open, and adaptive. Therefore, adaptive educational leadership plays a crucial role in driving relevant, effective, and sustainable educational transformation in the digital era. Keywords: adaptive leadership, digital education, educational transformation, digital literacy, organizational culture